Comparative genomic study of arachnid immune systems indicates loss of beta‐1, 3‐glucanase‐related proteins and the immune deficiency pathway. (22nd November 2015) - Bechsgaard, J.; Vanthournout, B.; Funch, P.; Vestbo, S.; Gibbs, R. A.; Richards, S.; Sanggaard, K. W.; Enghild, J. J.; Bilde, T.
Abstract: Analyses of arthropod genomes have shown that the genes in the different innate humoral immune responses are conserved. These genes encode proteins that are involved in immune signalling pathways that recognize pathogens and activate immune responses. These immune responses include phagocytosis, encapsulation of the pathogen and production of effector molecules for pathogen elimination. So far, most studies have focused on insects leaving other major arthropod groups largely unexplored. Here, we annotate the immune‐related genes of six arachnid genomes and present evidence for a conserved pattern of some immune genes, but also evolutionary changes in the arachnid immune system. Specifically, our results suggest that the family of recognition molecules of beta‐1, 3‐glucanase‐related proteins ( β GRPs) and the genes from the immune deficiency (IMD) signalling pathway have been lost in a common ancestor of arachnids. These findings are consistent with previous work suggesting that the humoral immune effector proteins are constitutively produced in arachnids in contrast to insects, where these have to be induced. Further functional studies are needed to verify this. We further show that the full haemolymph clotting cascade found in the horseshoe crab is retrieved in most arachnid genomes. Tetranychus lacks at least one major component, although it is possible that this cascade could still function through recruitment of a different protein. The gel‐forming protein in horseshoe crabs, coagulogen, was not recovered in any of the arachnid genomes; however, it is possible that the arachnid clot consists of a related protein, spätzle, that is present in all of the genomes.